Unlocking Blockchain’s Potential in Innovation Ecosystems: A Narrative Review - S, Uma (Novatio : Journal of Management Technology and Innovation, 2024)
Blockchain technology has emerged as a transformative enabler in innovation management. It offers new opportunities for enhancing transparency, improving efficiency, and fostering trust across diverse sectors.. This narrative review aims to synthesize existing literature on blockchain adoption, exploring its applications in supply chains, finance, public administration, and Industry 4.0, while analyzing systemic barriers to implementation. Literature searches were conducted across major databases such as Scopus, Web of Science, and Google Scholar using a structured methodology that employed primary and secondary keywords combined with Boolean operators. Inclusion criteria emphasized peer-reviewed studies from the past decade, encompassing both qualitative and quantitative approaches. The findings highlight blockchain’s role in enhancing supply chain traceability, reducing transaction costs, improving access to financial services, and strengthening governance models through decentralized systems. Integration with Industry 4.0 technologies further demonstrates blockchain’s capacity to improve efficiency, sustainability, and knowledge management. However, adoption remains constrained by technical complexity, scalability challenges, cultural resistance, and regulatory uncertainties. Comparative evidence underscores disparities between developed and developing economies, with the former focusing on high-value applications and the latter emphasizing accessibility and inclusion. The discussion emphasizes the need for supportive regulatory frameworks, capacity-building initiatives, and incentives for early adopters. Future research should address gaps through longitudinal, cross-industry, and sociotechnical studies to provide holistic insights into blockchain’s long-term implications. The study concludes that education, collaboration, and clear governance structures are central strategies to overcoming barriers and unlocking blockchain’s transformative potential for innovation management.